Il giallo-noir nella scrittura a quattro mani. Il caso di Acqua in bocca - Medaglia, Francesca (Incontri. Rivista europea di studi italiani, 2015)
Crime Fiction in Co-Authored Writing Practice. The Case Study of Acqua in bocca This article focuses on the issue of literary genres in relation to co-authored literature. In particular it analyzes the ways in which co-authored writing practice affects the authors’ choice of genre. In order to effectively investigate this issue, it surveys a set of literary works published by two or more authors in Western context from 1700 to 2013. This quantitative research leads to highlight some significant recurrent characteristics. In fact, it identifies crime novel and noir fiction as the most exploited ‘sub-genres’. To underline and exemplify this finding it analyzes Acqua in bocca by Andrea Camilleri and Carlo Lucarelli. This novel superbly underlines the main features of contemporary Italian crime-noir fiction: it is consumer-oriented, the authors’ style is creolized, and no more than two writers are involved. In addition, this work has other interesting features: the epistolary structure used in the text has the aim of charming the reader and well-known characters are used without altering their peculiarities beloved by their audience.